If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5g+5=14+2g
We move all terms to the left:
5g+5-(14+2g)=0
We add all the numbers together, and all the variables
5g-(2g+14)+5=0
We get rid of parentheses
5g-2g-14+5=0
We add all the numbers together, and all the variables
3g-9=0
We move all terms containing g to the left, all other terms to the right
3g=9
g=9/3
g=3
| 7+26m=42+19m | | 5y+14=7y+46 | | x-10=-15x-6 | | 3(4x+1)=3+12-5 | | 128÷8=o | | 4y+6=6y+24 | | y(y-31)=0 | | 3^x=3.5x | | m(m+23)=-132 | | ¾n-18=¼n-4 | | 7x-6x-3=8 | | -6=4-5x | | 12.89=2g+3.61 | | 51/5+13/10=x13 | | 7x+8-2=6-7x | | 3x-8=-1x | | F(x)=x(x)+6 | | 8x-7x-4=6 | | 10x-5=10x-2 | | -19+k=-38 | | 10x-5=4x+25 | | x5=1 | | 2x-12+4x=2-1x | | 51/5+13/1=13x | | -6+s=17 | | 7/8(z)=-2/9 | | 0.12x=120 | | |d|=-2 | | 11x-8x+10=3 | | 1/x+5-1/x+8=1/x+3-1/x+6 | | x2-3x=5x | | 8x-5+4x-7=180 |